Development and Validation of Catalytic Spectrophotometric Method for Trace Determination of Ruthenium - Prasad, Surendra (Asian Journal of Chemistry, 2012)
This paper describes highly sensitive, selective and rapid catalytic spectrophotometric method for the determination of trace amounts Ru(III). The method is based on the catalytic effect of Ru(III) on oxidation of benzylamine by alkaline hexacyanoferrate(III). The progress of reaction is followed by measuring the absorbance of the reaction mixture, i.e., disappearance of hexacyanoferrate(lII) at 420 nm. The calibration curves are linear in the range of 10 to 121 ng mL-1 of [Ru(III)] with detection limit 6.9 ng mL-1. The standard deviations and percentage errors for the determination of Ru[III] in the range of 10 to 121 ng mL-1 have been calculated. The influence of many interferents on the determination of Ru(III) has been examined. The method has been applied to the analysis of Ru(III) in synthetic samples. Recovery was found to be quantitative. The method is convenient and reliable with sort analysis time. The developed method permits the determination of Ru(III) concentrations down to 10 ng mL-1 with good accuracy and reproducibility.